FAKTOR-FAKTOR YA NG MENENTUKAN LOYALITAS PELANGGAN TERHADAP MEREK TEH BOTOL SOSRO DI KOTA DENPASAR - NI GUSTI AGUNG AYU ARIASTUTI; MADE ANTARA (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id, 2006)
One of effort to be company able to face the emulation is by creating and maintaining customer especiallyloyal customer because they represent the opportunity get the new customer and the end recurring purchasingwill be able to improve the sale and able to maintain the position which either in marketing.This research aim to know the factors determining customer loyalty to brand of Teh Botol Sosro andvariable deputizing every factor determining customer loyalty to brand of Teh Botol Sosro. This Researchstarted from date of 23 February 2005 up to 21 March 2005. This Research location selected by purposive inDenpasar town. Analysis used in this research as factor analysis that analysis which can be used to tracesome factor from a number indicator or variable determining customer loyalty to brand of Teh Botol Sosro.Result of analysis indicate that the factors determining customer loyalty to brand of Teh Botol Sosro thereis 7 factor, that is performance, features, conformance to specification, reliability/durability, serviceability,perceived quality, and esthetics. While variable deputizing every factor determining customer loyalty tobrand of Teh Botol Sosro there is 15 variable, that is product hygiene, as according to food, and productbenefit deputizing performance factor; company brand, feel the product, and size measure product deputizingfeatures factor; security consume and quality of packaging deputizing conformance to specification factor;product perfection to consumer and product resilience to all kinds of weather deputizing reliability/durabilityfactor; amenity obtain the product deputizing service factor; product price and company promotiondeputizing perceived quality factor; aroma of product and product color deputizing esthetics factor.Offer suggestion at company that is company can more selective again in useful life tidiness so thattidiness to consumer always good in a condition. Company also can make the sign of a period to going intoeffect bigger so that customer can know clearly what product which they buy still be competent or not to beconsumed. Company reputation have to be able defended by remain to yield the quality product so that willgenerate belief in society.